Tobacco use and associated mental symptoms and health risk behaviours amongst individuals 15 years or older in South Africa - Peltzer, Karl (S Afr J Psychiatr, 2020)
BACKGROUND: Tobacco use may deteriorate mental health and increase health risk behaviours. AIM: The aim of this investigation was to identify associations between tobacco use and mental illness symptoms and health risk behaviours in individuals 15 years or older in South Africa. SETTING: Community-based national population sample in South Africa. METHODS: Cross-sectional data were analysed from the ‘South African National Health and Nutrition Examination Survey (SANHANES-1) 2012’, using a sample of 15 310 individuals 15 years or older (median age 33 years). Measures included information on tobacco use, sociodemographic factors, mental symptoms and health risk behaviour. RESULTS: Compared to non-tobacco users, daily tobacco users were associated with psychological distress and post-traumatic stress disorder (PTSD) in adjusted logistic regression analysis, and with sleeping problems in unadjusted analysis. Past tobacco use, less than daily, and daily tobacco use were highly associated with a drinking problem. In terms of dietary variables, less than daily and daily tobacco use increased the odds of inadequate fruit intake and salty food intake, and daily tobacco use decreased the odds of fast food consumption. Past tobacco use, less than daily, and daily tobacco use were inversely associated with physical inactivity, and daily tobacco use was associated with not always washing hands before eating. CONCLUSIONS: The study showed that compared to non-tobacco users, daily tobacco users had significantly poorer mental health (psychological distress and PTSD) and increased odds for several health risk behaviours (drinking problem, inadequate fruit intake, salty food consumption and not always washing hands before eating) as compared to non-tobacco users.